GE_GERICHTE PM/1024/2014 vom 14. November 2016 - GE Cour de justice (2016)
CONDITION DE RECEVABILITÉ; OBJET DU RECOURS; TRAVAIL D'INTÉRÊT GÉNÉRAL; CONVERSION DE LA PEINE | CP.39; CP.393; PPMin.39; DPMin.23